Implementasi Pendidikan Karakter Melalui Program 3S (Salam, Sapa, Senyum) dan Tahsin di SDN 1 Cigadung - Puri, Rayanti; Inah, Tarsinah; Barnawi, Barnawi; Amirudin, Amirudin (Permata : Jurnal Pendidikan Agama Islam, 2023)
The management of students at Binaul Ummah Kuningan integrated Islamic Elementary School is still very lacking in maintaining the school environment. As an alternative to overcome this SDN 1 Cigadung apply character education in forming good moral students. The problem in this study is how practical education management in applying and forming students with noble character. The purpose of this study was to determine the management of integrated Islamic education in forming students with noble character by maintaining the environment at SDN 1 Cigadung Kuningan school, and knowing what are the supporting and inhibiting factors.This study uses a qualitative research approach with a descriptive qualitative research design. Data collection techniques used are interviews, observation, and documentation. This research method is a qualitative method, while the method of determining the subject using purposive sampling technique (random sample). After the data is collected, data analysis will be carried out, with data reduction steps, Data categories, data synthesis and conclusion.The results in this study revealed Student Management in improving student discipline are: first, the development of Student Management in improving student discipline SDN 1 Cigadung Kuningan is by trying to conduct student guidance on discipline through a program of daily, weekly, and monthly activities, the development of Student Discipline, Devotion in student development guidance,enforcement of student discipline. Secondly, the active role of parents. Third, adequate school facilities. Fourth, quality teachers and the assistant teacher. While the inhibiting factor is the lack of communication between parents and teachers, the lack of facilities used, students experience fatigue (partly) as well as teachers who feel fatigue from activities at school.Keyword: Character Education; Greetings; Smiles. Abstrak Manajemen peserta didik di Sekolah Dasar Islam Terpadu Binaul Ummah Kuningan masih sangat kurang di dalam menjaga lingkungan sekolah. Sebagai alternatif dalam mengatasi hal tersebut SDN 1 Cigadung menerapkan pendidikan karakter dalam membentuk siswa berahlak mulia. Permasalahan dalam penelitian ini adalah bagaimana manajemen Pendidikan yang berkrakter di dalam menerapkan dan membentuk siswa berakhlak mulia. Tujuan penelitian ini adalah untuk mengetahui manajemen Pendidikan Islam Terpadu dalam membentuk siswa berakhlak mulia dengan menjaga lingkungan disekolah SDN 1 Cigadung Kuningan, serta mengetahui apa saja faktor pendukung dan penghambatnya.Penelitian ini menggunakan pendekatan penelitian kualitatif dengan rancangan penelitian deskriptif kualitatif. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi. Metode penelitian ini adalah metode kualitatif, sedangkan metode penentuan subjek menggunakan teknik purposive sampling (sample secara acak). Setelah data terkumpul maka akan dilakukan analisis data, dengan langkah-langkah reduksi data, kategori data, sintesis data dan penarikan kesimpulan.Hasil dalam penelitian ini mengungkapkan manajemen kesiswaan dalam meningkatkan kedisiplinan siswa adalah: Pertama, pengembangan manajemen kesiswaan dalam meningkatkan kedisiplinan siswa SDN 1 Cigadung Kuningan yaitu dengan berupaya melakukan pembinaan siswa tentang kedisiplinan melalui program kegiatan harian, mingguan, dan bulanan, pengembangan disiplin siswa, pengabdian dalam pembinaan pengembangan siswa,penegak disiplin siswa. Kedua, peran aktif orang tua. Ketiga, sarana fasilitas sekolah yang memadai. Keempat, guru berkualitas dan guru pendamping. Sedangkan faktor penghambatnya adalah minimnya komunikasi orang tua dan guru, minimnya sarana yang digunakan, peserta didik mengalami kecapean (sebagian) begitu juga dengan guru yang merasa keletihan dari aktivitas di sekolah.Kata Kunci: Pendidikan Karakter; Salam; Sapa; Senyum.